PARTISIPASI ORANG MUDA KATOLIK DALAM DUNIA POLITIK: TINJAUAN SISTEMATIK LITERATURE - Abraham, Agustinus (Bahasa Indonesia, 2025)
Politics is seen as an endeavor in co-creating, progressing the nation and state. All citizens are expected to actively participate in these endeavors. Catholic Youth are also not free from political participation. The purpose of this paper is to find out the form of Catholic participation in politics and the factors that encourage them. This research uses the Systematic Literature Review (SLR) method with a qualitative descriptive approach. This SLR adopts the Preferred Items for Systematic Reviews and Meta-Analysis (PRISMA). The results in this study show that Catholic Youth have participated in politics with various forms of participation and are driven by several external factors. The most common form of political participation provided by Catholic Yout is education, both formal education and informal education. In addition, they also provide participation in the form of direct involvement in politics. Some of them became the success team of one of the candidate pairs in a general election. The factors that influence them are family, religious leaders, and teachers.